2016
DOI: 10.1111/ina.12283
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde and acetaldehyde exposure and risk characterization in California early childhood education environments

Abstract: Little information is available about air quality in early childhood education (ECE) facilities. We collected single-day air samples in 2010-2011 from 40 ECE facilities serving children ≤6 years old in California and applied new methods to evaluate cancer risk in young children. Formaldehyde and acetaldehyde were detected in 100% of samples. The median (max) indoor formaldehyde and acetaldehyde levels (μg/m ) were 17.8 (48.8) and 7.5 (23.3), respectively, and were comparable to other California schools and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 33 publications
(40 reference statements)
1
27
1
Order By: Relevance
“…In turn, Yang, et al [33] also identified emission from construction and furnishing materials as a possible cause for the increase of CH 2 O concentrations. A recent study carried out by Bradman, et al [58], in 40 early childhood education facilities in California serving children aged 6 years or less, also detected CH 2 O at all sampling sites with values lower (max = 48.8 µg/m 3 ) than those measured in the present study.…”
Section: Resultscontrasting
confidence: 51%
“…In turn, Yang, et al [33] also identified emission from construction and furnishing materials as a possible cause for the increase of CH 2 O concentrations. A recent study carried out by Bradman, et al [58], in 40 early childhood education facilities in California serving children aged 6 years or less, also detected CH 2 O at all sampling sites with values lower (max = 48.8 µg/m 3 ) than those measured in the present study.…”
Section: Resultscontrasting
confidence: 51%
“…In another Californian study, the mean FA concentration was 34 µg/m 3 in homes built with low-emitting materials and 46 µg/m 3 in conventional homes at an air exchange rate of 0.35 h −1 (Hult et al 2015). Furthermore, 40 early childhood education facilities were studied in California; the arithmetic mean FA concentration was 19 µg/m 3 with a range from 0.7 to 49 µg/m 3 (Bradman et al 2016). In houses inhabited by asthmatics in the Boston area, the geometric mean FA concentration was 43 µg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, using effective means to reduce indoor air pollution and improve air quality are important issues for building occupants and users in nonventilated places, like hospitals and laboratories (Brown et al, 2015;Lucas et al, 2016;Verriele et al, 2016;Bradman et al, 2017). Indoor air handling systems with HEPA filters control the ambient environmental conditions, including the temperature, humidity, air flow and air cleaning (Russell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%